The Development of PowerPoint-Based Video Intructional Media for Islamic Education Teachers in MTs Qudsiyyah Kudus - Guntur Cahyono; Muhamad Rozikan (Universitas Sebelas Maret, 2022)
This research aims to develop a PowerPoint-based video instructional media. PowerPoint is an office application that teachers can easily operate. There are three steps in the development process of this research, namely, testing the prototype of the material on individual students with three students. It was followed by trials in small classes and large class trials (field tryouts). This small class trial involved eight students, while the large class involved 20 students by taking the students in the class. The first evaluation results of this learning media product were 89.9, followed by the second and third tests, which resulted in the same score of 89.3. It means that the design development of this media product is feasible for the teaching and learning process and can be developed according to the learning needs of the madrasah. The evaluation and product improvement process needs to be carried out to produce good learning media products. This PowerPoint-based video learning media is expected to provide new learning experiences for students because learning is more interesting.